Manual de funciones de talento humano de apuestas nacionales de Colombia S.A.S - Merchan Zuleta, Cristian Roberto (Universidad Antonio Nariño, 2023)
In the first place, when we sat down with my boss and analyzed how everything was being carried out, the functions manual was found to be faulty, since it was seen that everyone was going their own way or that they simply were not doing the right thing, or in other The cases did tasks that the other person had to do, and we are not talking about that being bad because being companions helps to improve and be a good person, but it was seen that it was not the best option because the one who was helped was taking away the relevant functions and that is where the manual of functions of Apuestas Nacionales de Colombia S.A.S begins to be implemented, charge by charge is taken and feedback is given which will lead to highlighting the corresponding functions, all this from the beginning of the volume. in a very good way since each individual took a sense of belonging for their functions and took it with more dedication, although this implementation is recent little by little with the daily and weekly control that is is doing leads to great benefits since tasks that were left aside now is the exact moment to carry them out, on the other hand I help to identify what are the daily activities and characteristics of each of the positions, determining the procedures that are must comply, leading them to a responsibility that must be taken in the face of this situation